(untitled) (Conferencea, 2023)
This article explores the paradigm of nepotism in Russian and Uzbek proverbs and sayings. Both cultures have a long history and rich heritage, and their proverbs and sayings reflect the nuances and attitudes towards nepotism prevalent in their respective societies.